2021
DOI: 10.3174/ajnr.a7007
|View full text |Cite
|
Sign up to set email alerts
|

Altered Processing of Complex Visual Stimuli in Patients with Postconcussive Visual Motion Sensitivity

Abstract: BACKGROUND AND PURPOSE: Vestibular symptoms are common after concussion. Vestibular Ocular Motor Screening identifies vestibular impairment, including postconcussive visual motion sensitivity, though the underlying functional brain alterations are not defined. We hypothesized that alterations in multisensory processing are responsible for postconcussive visual motion sensitivity, are detectable on fMRI, and correlate with symptom severity. MATERIALS AND METHODS:Twelve patients with subacute postconcussive visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…There is considerable interest and ongoing effort to characterize the cortical network subserving vestibular function and recent clinical and neuroimaging studies evince complex interactions between central vestibular substrates and cognitive, oculomotor, and emotional/affective domains (Indovina et al, 2020; Raiser et al, 2020). Brain regions involved in visuospatial, affective, and integrative functions also subserve vestibular processing, modulate oculomotor gain and visual attention, and may contribute to dysfunction in a subset of syndromes including PPPD and PCVD (Allen et al, 2021; Passamonti et al, 2018; Riccelli et al, 2017; Trofimova et al, 2021). This study is, to our knowledge, the first to situate these ancillary connections in the larger context of vestibular function and dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is considerable interest and ongoing effort to characterize the cortical network subserving vestibular function and recent clinical and neuroimaging studies evince complex interactions between central vestibular substrates and cognitive, oculomotor, and emotional/affective domains (Indovina et al, 2020; Raiser et al, 2020). Brain regions involved in visuospatial, affective, and integrative functions also subserve vestibular processing, modulate oculomotor gain and visual attention, and may contribute to dysfunction in a subset of syndromes including PPPD and PCVD (Allen et al, 2021; Passamonti et al, 2018; Riccelli et al, 2017; Trofimova et al, 2021). This study is, to our knowledge, the first to situate these ancillary connections in the larger context of vestibular function and dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…An association between vestibular provocation and insular recruitment in controls, but not in PPPD participants, was reported in the same study (Riccelli et al, 2017). Similarly, it was recently reported that control participants and patients with subacute post‐concussive vestibular dysfunction (PCVD) exhibit differential recruitment of the visual, parieto‐insular, parietal, frontal, and cingulate cortices and hippocampus in response to visual‐vestibular provocation, and noted that activity in the frontal eye field, posterior hippocampus, and middle temporal visual area (hMST/V5) was associated with Vestibular Ocular Motor Screening (VOMS: Mucha et al, 2014) scores across all control and PCVD participants (Allen et al, 2021). Subjects with higher resting‐state connectivity between the posterior hippocampus and ipsilateral V5, and among the left and right‐hemisphere MSO, PIVC, and right anterior insula, have also been shown to exhibit increased symptoms during VOMS testing (Trofimova et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Altered vestibular function has been hypothesized to cause postconcussive visual motion sensitivity. Allen et al found that post-concussion patients with subacute vestibular impairment symptoms showed exaggerated activation in the multisensory processing centers involved in visual-vestibular sensory processing [119]. They hypothesize that these patients developed overreliance on visual stimuli to compensate for vestibular impairment and that this may lead to difficulty in recovering after TBI.…”
Section: Vestibular Systemmentioning
confidence: 99%
“…Moreover, multimodal sensory management requirements incur a greater processing demand for persons with prior mTBI ( 110 112 ). Compromised multimodal sensory management of visual-vestibular stimuli is commonly found in persons with mTBI ( 110 113 ). The added processing challenges of multimodal signals often leads to impaired cognition well past the onset of mTBI.…”
Section: Altered Sensory Processing White Matter Pathology and Cognit...mentioning
confidence: 99%